Legal Implications of Deep Seabed Mining on the Sustainability of the Blue Economy in Indonesia - Edward Michael Harapan Simangunsong; Muhammad Faisal Hamdi; Anisa Latifah Rahman Lubis; Fariss Febrian; Benny Sumardiana (Green Publisher, 2024)
This research examines the legal implications of deep seabed mining on blue economy sustainability. Indonesia, as an archipelagic country, has enormous marine potential that needs to be managed with a blue economy approach to support sustainable economic growth and community welfare. This research uses a normative legal method with a statutory approach to analyze various related regulations. The results show that deep seabed mining can make a significant contribution to the economy, especially through the extraction of minerals such as nickel, copper and cobalt. However, this activity also poses serious environmental risks, including damage to marine ecosystems and increased carbon emissions that impact climate change. Therefore, a comprehensive and sustainable regulatory framework is needed, integrating blue economy and precautionary principles to ensure that the exploitation of deep-sea resources is carried out responsibly and sustainably.